2003
DOI: 10.1007/s00066-003-1062-8
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy for Stage I–III Nodal Low-Grade Non-Hodgkin’s Lymphoma

Abstract: Our results maintain external radiotherapy as a curative concept in the treatment of limited stage low-grade lymphoma, especially in younger patients. Patterns of recurrence would favor total nodal irradiation (TNI) as an appropriate approach for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 36 publications
4
19
1
1
Order By: Relevance
“…In some studies 20-30 Gy were sufficient and relapses were only observed with radiation doses < 20 Gy [2,27]. However, doses up to 36 Gy seem to be able to control > 90% of the most common, indolent orbital NHLs [14,18,22,26]. Contrarily, the dose for intermediate and aggressive orbital NHLs is not well defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies 20-30 Gy were sufficient and relapses were only observed with radiation doses < 20 Gy [2,27]. However, doses up to 36 Gy seem to be able to control > 90% of the most common, indolent orbital NHLs [14,18,22,26]. Contrarily, the dose for intermediate and aggressive orbital NHLs is not well defined.…”
Section: Discussionmentioning
confidence: 99%
“…The role of chemotherapy in the treatment of indolent stage IE orbital lymphoma is limited [6,17,22]. On the one hand, systemic therapy alone is not sufficient for local control, whereas on the other hand, long-term survival is not influenced by adjuvant chemotherapy directly after radiation treatment [6].…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy aimed at treating the entire head skin with a dose as homogeneous as possible to a depth of 3 mm applying a total dose of 36 Gy in single doses of 2.0 Gy five times a week according to commonly accepted involved-field treatment regimens for low-grade non-Hodgkin's lymphoma [2,6,8,13].…”
Section: Introductionmentioning
confidence: 99%
“…Since FL is considered to be one of the most radiosensitive tumours, [93][94][95] the role of radiotherapy (RT) as consolidation treatment of regions with bulky disease after completion of chemotherapy has been investigated.…”
Section: Role Of External Beam Radiotherapy As Consolidation Therapy mentioning
confidence: 99%